REPRESENTASI MAKNA MATERIALISME PADA VIDEO KLIP LAGU MONEY - Jeanie Annissa; Ricky Widyananda Putra (Jurnal Komunikasi, 2024)
This paper discusses about the analysis of the meaning of materialism in the video clip of the song "Money" sung by Lisa Blackpink from South Korea. The video clip contains the meaning of materialism by visually and the song text which shows materialism which includes material values which are visualized through certain movements and the selection of diction in the lyrics sung on social media youtube on the BlackPink account. The video clip is widely played and decorates social media. Thus, this study shows the perspective of teenagers on the representation of the meaning of materialism through the video clip of the song. This study uses the semiotic triangle meaning theory which refers to the sign, object, and interpretation using a qualitative methodology using a constructivist approach through primary data collection techniques in the form of non-participant observation. and secondary data which includes library data by 20 books, 13 journals, and 10 online sources. The results of this study indicate that the representation of the meaning of materialism in the video clip of the song Money sung by Lisa BlackPink which is analyzed from the visualization of dance movements and the text of the song lyrics is divided into 7 points which include elements of money, self-centered, hedonism, consumerism, the domination of money power, hard work and happiness. All of them are analyzed by visualization of images and song texts.